Digital libraries in the classroom: Secondary school teachers’ conception - A Abrizah; AN Zainab (Journal of Librarianship and Information Science, 2011)
This paper presents findings from a case study investigating secondary school teachers’ understanding of the term digital libraries and their relationship with learning. The study addresses two research questions: (1) How do teachers conceptualize digital libraries, their relevance and issues relating to their integration into the curriculum? and (2) What are the teachers’ perceptions of the initiative to develop a collaborative digital library for school projects? A series of interviews were carried out on six History subject teachers which provide a detailed and succinct information on their understanding of digital libraries, their knowledge and use of the Internet and digital resources, their perception of the possible impact of digital resources on teaching and learning, the benefits teachers seen in digital resources and the problems they have in using them. It also offers important insights on History subject teachers’ perceptions of the initiative to develop a collaborative digital library for History projects, perception of its potential use, pointing out the conditions that facilitate its use in the classrooms. The paper also points out the relevance of digital libraries to the History curriculum which will make readers understand that using the technology is relevant to the teaching of all subjects.
Keywords: digital libraries; écriture et lecture numériques; enseignement secondaire

Digital libraries in the classroom: Secondary school teachers’ conception - A Abrizah; AN Zainab (2011)